210Po and 210Pb as tracers for particle cycling in a shallow semi-enclosed bay of Taiwan Strait. (February 2023) - Zhong, Qiangqiang; Guo, Wenyi; Wang, Hao; Ji, Jianda; Lin, Jing; Du, Jinzhou; Huang, Dekun; Yu, Tao
Abstract: Naturally-occurring 210 Po and 210 Pb are good tracers for particle cycling in the estuarine and coastal environment. Activities of 210 Po and 210 Pb were measured in samples of bulk (wet + dry) atmospheric deposition, river water and surface seawater collected in the Zhangjiang Estuary-Dongshan Bay to investigate the geochemical scavenging rates (or residence times) of these particle-reactive nuclides. The spatial distribution of 210 Po and 210 Pb were strongly influenced by suspended particulate matter (SPM) concentrations and in almost all stations, 210 Po and 210 Pb were mainly in particulate form (51.7%–92.2% of the total for 210 Po and from 44.3% to 90.3% for 210 Pb). Due to the very high SPM concentration, enhanced scavenging of 210 Po and 210 Pb was observed in the maximum turbidity zone of Zhangjiang River, with a marked decrease of dissolved nuclides' activities. We built a mass balance model and we found out that atmospheric inputs are the major source of these radionuclides comparing with other sources (e.g., river inputs or ingrowth production) in the study area. Residence times of 210 Pb were calculated to be 2.2–9.8 and 0.5–8.9 days for dissolved and particulate 210 Pb, respectively. And residence times of dissolved and particulate 210 Po were 6.3–31.7 and 2.2–13.9 days, respectively. In the turbidity zone, we found an unexpected result that particulate 210 Po and 210 Pb had the longest residence times (about two weeks), suggesting that SPMs in the turbidity zone would not be easy to sink to the sea floor. We also found that different SPMs showed significantly different 210 Po/ 210 Pb activity ratios, which increased in the following order: atmospheric deposition in dry season < SPMs in river < SPMs in the Zhangjiang Eastuary-Dongshan Bay < biogenic particles (including detritus, fecal pellets, cells of phytoplankton and zooplankton). This phenomenon implied that 210 Po/ 210 Pb activity ratio in the particles has the potential application in distinguishing SPM sources in the coastal seas. Highlights: Distribution of 210 Po and 210 Pb in estuary and bay were strongly influenced by SPMs. Enhanced scavenging of 210 Po and 210 Pb occurred in the turbidity zone. SPMs from different sources showed significantly different 210 Po/ 210 Pb activity ratios. τ( 210 Po) and τ( 210 Pb) in the turbidity maximum zone were much longer than other regions.